The effects of reward systems in prison: A systematic review - Elbers, Jan Maarten (International journal of law, crime and justice, 2022)
Introduction Using rewards to influence behavior and attitudes of incarcerated individuals is historical, widespread, and becoming increasingly popular. Surprisingly, little is known on the effectiveness of reward systems in prison (RSPs). This paper aims to address this gap. Method. A systematic review on RSPs was conducted, twenty one studies met the inclusion criteria. Results. Overall, findings on RSP effectiveness were mixed. Three study types were identified. Type-1 studies indicated that experimental RSPs using tokens yield positive short-term behavioral effects in individuals cognitively functioning below average. Type-2 studies indicated that non-experimental RSPs are most successful when targeting high-risk participants and include cognitive program elements. Type-3 (qualitative) studies highlight three potential moderators: a pain of self-government, perceived legitimacy, and using family contact as a reward. Discussion. As overall study quality is below average, findings should be interpreted with caution. Results were partially congruent with prior research.